Hasil Pelatihan Digital Marketing Pada Umkm Desa Kaliacar Gading Probolinggo - Maghfirotul Hamdiah; Yulida Fithriyatul Maini (Najah: Journal of Research and Community Service, 2026)
Micro, small and medium enterprises have experienced significant developments from time to time. The business people also produce various types, various products and services. Micro, small and medium enterprises are also one of the breakthroughs to improve the community's economy to achieve adequate living welfare. It is hoped that MSME actors will be able to reduce unemployment in the midst of global economic competition. One example of the existence of UMKM Es Puter Kaliacar is expected to be able to support the economy both individually and as a group by following the trend of the times so that they are always ready to face global competition. One of them is by applying information and communication technology to support its business activities. This activity method uses the ABCD (Asset Based Communities Development) method which is an approach model in community development. This approach emphasizes an inventory of assets in the community that are seen as supporting community empowerment activities. Digital marketing is an information technology product in the form of product promotion activities via the internet. Utilizing digital marketing to support business activities has proven to be able to increase the income of UMKM Kaliacar es puter and able to provide new innovations for makers of Kaliacar es puter products.